Discriminative Sparse Features for Alzheimer’s Disease Diagnosis using multimodal image data. - Ortiz-García, Andrés; Lozano Cuadra, Federico; Górriz-Sáez, Juan Manuel; Ramírez-Aguilar, Francisco Javier; Martínez-Murcia, Francisco Jesús (Bentham Science, 2018)
Feature extraction in medical image processing still remains a challenge, especially in high-dimensionality datasets, where the expected number of available samples is considerably lower than the dimension of the feature space. This is a common problem in real-world data, and, specifically, in medical image processing as, while images are composed of hundreds of thousands voxels, only a reduced number of patients are available. Extracting descriptive and discriminative features allows representing each sample by a small number of features, which is particularly important in classification task, due to the curse of dimensionality problem. In this paper we solve this recognition problem by means of sparse representations of the data, which also provides an arena to multimodal image (PET and MRI) data classification by combining specialized classifiers. Thus, a novel method to effectively combine SVC classifiers is presented here, which uses the distance to the hyperplane computed for each class in each classifier allowing to select the most discriminative image modality in each case. The discriminative power of each modality also provides information about the illness evolution; while functional changes are clearly found in Alzheimer’s diagnosed patients (AD) when compared to control subjects (CN), structural changes seem to be more relevant at the early stages of the illness, affecting Mild Cognitive Impairment (MCI) patients. Finally, classification experiments using 68 CN, 70 AD and 111 MCI images and assessed by cross-validation show the effectiveness of the proposed method. Accuracy values of up to 92% and 79% for CN/AD and CN/MCI classification are achieved.
Keywords: Alzheimer, Enfermedad de - Diagnóstico por imagen - Proceso de datos; Diagnóstico - Proceso de datos; Medicina - Proceso de datos; ADNI; Sparse features; Computer aided diagnosis; Mild cognitive impairment; Multimodel data; Support vector classifiers